Pedagogisti e educatori tra scuola e università - Cives, Giacomo (Filosofia dell'Educazione, 2018)
Due to his firm belief in the value of a close cooperation between school and university, and also in the commitment to the creation of a form of emancipatory and democratic education, the author collected profiles and accounts relating to his personal meeting with educationalists (as well as philosophers who were interested in the topic of education) and scholars fighting together to create a liberating school accessible to everyone. Therefore, the pages on Raffaele Resta, Giovanni Calò, Franco Lombardi and Luigi Volpicelli (both former teachers of the author), Dina Bertoni Jovine, Remo Cantoni, Marco Olivetti, Angelo Broccoli, Dina Tomasi, Santoni Rugiu, Remo Fornaca are joined by those on the school principals Virgilio Zangrilli, Giacomo Santucci, Giustino Broccolini (who then became associate professor). All of these are generous people, engaged in wide prospects and constructive, educational and civil programs, without falling victim to the narrow technical specializations or lack of horizons.